The Role of Technology in Improving Language Skills in Education (Indo-MathEdu Intellectuals Journal, 2023)
Language is one of the key aspects in human development and the educational process. Technology has become one of the major forces shaping education. This research aims to further examine the role of technology in improving language skills in education. This research uses a qualitative methodology in the form of a literature review, which implies that the research will examine and explain data by utilising information and textual content from various sources. Data analysis techniques included content analysis to identify patterns and themes in the literature, theme analysis to understand the framework, coding to categorise data, constant comparison analysis to compare data, synthesis of findings, and triangulation to validate analysis results. The results show that technology plays a very important role in improving language proficiency in education. In the digital era, wider access to learning resources, technology-based learning applications, adaptive learning, and the use of technology in the classroom have opened up great opportunities for students to improve their language skills